2014
DOI: 10.5958/j.0976-0563.33.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic treatment on juice yield, viscosity and clarity of banana juice

Abstract: The effect of pectinase enzyme concentration (0.05 0.15%), incubation temperature (30-50''C) and incubation time (60-180 min) on juice yield, viscosity and clarity of banana juice were studied. A Central Composite Design was used to optimize the conditions for enzymatic clarification of banana pulp to maximize juice yield and clarity and to minimize pulp viscosity. Significant regression model describing the changes of juice yield, viscosity and clarity of juice with respect to hydrolysis paramètres were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Pectinex Ultra SP-L and cellulase enzyme i.e. Celluclast 1.5L as per the process suggested by Tapre and Jain (2014). The banana fruits were washed, peeled manually and cut into small pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Pectinex Ultra SP-L and cellulase enzyme i.e. Celluclast 1.5L as per the process suggested by Tapre and Jain (2014). The banana fruits were washed, peeled manually and cut into small pieces.…”
Section: Methodsmentioning
confidence: 99%
“…The enzymatic hydrolysis of pulp improved the juice yield and quality, in terms of viscosity, clarity. The enzymatic method was industrially applicable to improve the yield and quality of the juice [7]. The enzymes, mainly pectinases, assist in pectin hydrolysis, which cause a reduction in pulp viscosity and a significant increase in juice yield [8].…”
Section: Introductionmentioning
confidence: 99%
“…The juice yield was increased by 11.38%. Tapre and Jain [24] evaluated the effect of pectinase enzyme concentration (0.05% to 0.15%), incubation temperature (30°C to 50°C) and incubation time (60-180 min) on juice yield and clarity of banana pulp. They found that 0.11% enzyme concentration at 39.8°C, incubation for 143 min achieved maximum juice yield of 75.11% and clarity of 94.05%.…”
Section: Introductionmentioning
confidence: 99%